A metacognição de usuários no processo de busca da informação em catálogo coletivo de biblioteca universitária - Dal'evedove, Paula Regina; Neves, Dulce Amélia De Brito; Fujita, Mariângela Spotti Lopes [UNESP] (Escola de Ciência da Informação da UFMG, 2014)
It was observed the metacognitive trajectory of three users from a public university library the state of Sao Paulo to identify the metacognitive strategies that were used during the process of searching for information in a online collective catalog. Its configuration was based on participants' oral reports obtained by the technique of individual verbal protocol to provide an actual configuration of the task ans a closer examination of its natural recovery of information systems. The data collection sessions were recorded, and the recorded data were transcribed and categorized into four units of analyses: 1- expertise, 2-regulation, 3-assessment of knowledge itself and 4- organization of cognitive process. The results showed that knowledge of meta-cognitive strategies affects the quality of the results obtained in the process of searching for information and interferes in the way it implements retrieval on-line catalog, a fact the emphasizes the need for studies to move forward on issues meta-cognition of users of information.

Observou-se a trajetória metacognitiva de usuários de uma biblioteca universitária a fim de identificar as estratégias metacognitivas utilizadas durante o processo de busca da informação em catálogo coletivo online. Sua configuração foi pautada nos relatos orais dos sujeitos participantes obtidos por meio da técnica do Protocolo Verbal Individual de modo a propiciar uma configuração real da tarefa e uma análise mais aproximada do seu fazer natural em sistemas de recuperação da informação. Os resultados demonstram que o conhecimento de estratégias metacognitivas repercute na qualidade dos resultados obtidos no processo de busca da informação e interferem no modo como se concretiza a recuperação da informação em catálogo online, fato que acentua a necessidade de estudos que avancem em questões relacionadas à metacognição de usuários de informação.
The metacognition of users in the process of information search in collective catalogs of university library
Keywords: Metacognição; Comportamento informacional; Processo de busca da informação; Usuário de informação; Biblioteca universitária; Metacognition; Information behavior; Process of information search; User information; University library